2013
DOI: 10.1016/j.jprot.2013.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Time-course proteomic analysis of taurocholate-induced necrotizing acute pancreatitis

Abstract: Acute pancreatitis is an inflammatory disease of the pancreas, which varies greatly in course and severity. Severe forms are associated with serious local and/or systemic complications, and eventually death. The pathobiology of acute pancreatitis is complex.Animal models have been developed to investigate pathobiological processes and identify factors determining disease course. We performed a time-course proteomic analysis using a rat model of severe necrotizing acute pancreatitis induced by taurocholate perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…A rat model of SAP was established in this study using STC-induced pancreatitis, which has been widely used and is the most successful model of the evolution of AP ( 9 ). Tissue edema, leukocyte infiltration, acinar cell necrosis, and hemorrhage were the pathological changes observed in this model.…”
Section: Discussionmentioning
confidence: 99%
“…A rat model of SAP was established in this study using STC-induced pancreatitis, which has been widely used and is the most successful model of the evolution of AP ( 9 ). Tissue edema, leukocyte infiltration, acinar cell necrosis, and hemorrhage were the pathological changes observed in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium taurocholate-induced pancreatitis in mice or rats is the most well-characterized model of pancreatitis. This model has been extensively employed for probing events that may be critical to the evolution of pancreatitis [ 11 ]. These pathological changes include the colocalization of lysosomal hydrolases with digestive enzyme zymogens in cytoplasmic vacuoles, the intra-acinar cell activation of trypsinogen, and the activation of NF-κB and p38MAPK [ 12 ],[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…As increasingly diverse functions of Reg3α were reported (9-11), we refined the investigation to focus on the expression and localization of Reg3α immunoreactivity in the murine diabetic pancreas (Supplemental Figure 3). Reg3α previously was considered as expressing in non-β-cells of NOD islets and the acinar epithelium (27)(28)(29). We further showed that Reg3α expression was restricted mainly to pancreatic α cells of streptozotocin-induced diabetic models, the colocalization of Reg3α and glucagon immunoreactivity was predominant.…”
Section: Discussionmentioning
confidence: 60%